NURSING KNOWLEDGE OF OXIGENOTHERAPY - Liandra Grando; Cláudia Silveira Viera (Universidade Federal de Goias, 2002)
The purpose of this study was to identify the knowledge of the nurses team about the sequels thatthe oxigentherapy may cause to the newborns and how to make the nurses care. The research was qualitativeaccording to MINAYO (1996) and applied to the nurses team of an intensive care for newborns. The analysis wasbased in two categories: the nurses care for the newborn in oxigentherapy and the nurses team perception aboutsome possible sequels to the newborn in oxigentherapy. It was possible to observe that the care was appliedwithout any standardization and the knowledge about this problem is not enough.